HYPOGLYCEMIC EFFECT OF TRECULIA AFRICANA DECNE ROOT BARK IN NORMAL AND ALLOXAN-INDUCED DIABETIC RATS. - Oyelola, O. O.; Moody, J. O.; Odeniyi, M. A.; Fakeye, T. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2007)
The solvent partitioned purified fractions of the hydro-acetone root bark extract of the African breadfruit (Treculia africana Decne) were evaluated for hypoglycemic activities in normal and diabetic albino rats. Fasting blood glucose levels were estimated by the use of a glucometer at pre-determined intervals after oral administration of the test extracts/fractions. Results revealed that the test fractions have only a slight effect on blood sugar level of normal rats. On short term and chronic administration in diabetic rats however, diethyl ether-soluble (DEF) and the water-soluble (WSF) fractions significantly reduced the fasting blood sugar levels (p<0.05) at differing rates when compared with the control group of animals. The diethyl ether soluble fraction (10 mg kg-1 dose level) was found to exhibit the highest activity giving 69.4% reduction in blood sugar level (at 240 hours) which was in comparable range with the reference standard glibenclamide (0.5 mg kg-1) which reduced blood sugar levels by 65.8% below the initial baseline values.